2016
DOI: 10.1038/srep35490
|View full text |Cite
|
Sign up to set email alerts
|

PolyHIPE Derived Freestanding 3D Carbon Foam for Cobalt Hydroxide Nanorods Based High Performance Supercapacitor

Abstract: The current paper describes enhanced electrochemical capacitive performance of chemically grown Cobalt hydroxide (Co(OH)2) nanorods (NRs) decorated porous three dimensional graphitic carbon foam (Co(OH)2/3D GCF) as a supercapacitor electrode. Freestanding 3D porous GCF is prepared by carbonizing, high internal phase emulsion (HIPE) polymerized styrene and divinylbenzene. The PolyHIPE was sulfonated and carbonized at temperature up to 850 °C to obtain graphitic 3D carbon foam with high surface area (389 m2 g−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…Thus, Figure a reveals that sponge-like morphology, which is composed of interconnected spherical particles with some elongations creating the tendency to grow further. These interconnected Ni 2 P nanoparticles interweaved together forming the more significant bulk of an open spongy structure . By the side of 24 h, Scheme clarifies the phenomena of integration of individual particles getting merged making hefty particles leading to reduced porosity with the support of sufficient reaction time.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, Figure a reveals that sponge-like morphology, which is composed of interconnected spherical particles with some elongations creating the tendency to grow further. These interconnected Ni 2 P nanoparticles interweaved together forming the more significant bulk of an open spongy structure . By the side of 24 h, Scheme clarifies the phenomena of integration of individual particles getting merged making hefty particles leading to reduced porosity with the support of sufficient reaction time.…”
Section: Resultsmentioning
confidence: 82%
“…These interconnected Ni 2 P nanoparticles interweaved together forming the more significant bulk of an open spongy structure. 52 By the side of 24 h, Scheme 1 clarifies the phenomena of integration of individual particles getting merged making hefty particles leading to reduced porosity with the support of sufficient reaction time. This results in the emergence of Ni 12 P 5 phase in the Ni 2 P crystal structure, picked up earlier.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 97%
“…It has been reported that microporosity and mesoporosity imbue such materials with a high surface area, while accessibility to their sorption sites is determined by their hydrophobicity and macroporosity. 13 Several methods have been reported for the construction of 3D graphene, such as carbonisation of a polymer framework, 14 freeze-drying, 15 sugar-blowing, 16 cross-linking assembly 17 and the Pickering emulsion technique. 18 Given its advantages in terms of cost, quality and sustainability, the demand for applications based on the Pickering emulsion technique has begun to increase in various industries.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for the construction of 3D graphene, such as carbonisation of a polymer framework, 14 freeze-drying, 15 sugar-blowing, 16 cross-linking assembly 17 and the Pickering emulsion technique. 18 Given its advantages in terms of cost, quality and sustainability, the demand for applications based on the Pickering emulsion technique has begun to increase in various industries.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the macroporous morphologies of the carbon monoliths are often strikingly similar to those of the original polyHIPEs, in spite of the extensive reductions in mass and volume. The polyHIPEs used for generating carbons have been based on styrenics, 59,66–70 acrylonitrile, 71–73 tannin, 74 phenolics, 75,76 furfuryl alcohol, 77 Kraft black liquor, 78 polycarbosilane 79 and urea‐based precursors 80 . Porous carbons combining macroporosity with microporosity and mesoporosity ( S BET as high as 900 m 2 g −1 ) were generated by combining several types of templating, often including the use of hybrid or silica frameworks 81–85 ; oxygen and nitrogen functionalities in polyHIPE‐derived carbons have been obtained using oxygen‐ or nitrogen‐containing monomers 5,57,86 ; and chemical activation has been used to generate microporosity ( S BET as high as 2000 m 2 g −1 ) in carbonized polyHIPEs 63,87 .…”
Section: Introductionmentioning
confidence: 99%